2016
DOI: 10.1016/j.ijpharm.2016.08.046
|View full text |Cite
|
Sign up to set email alerts
|

A design space exploration for control of Critical Quality Attributes of mAb

Abstract: A unique "design space (DSp) exploration strategy," defined as a function of four key scenarios, was successfully integrated and validated to enhance the DSp building exercise, by increasing the accuracy of analyses and interpretation of processed data. The four key scenarios, defining the strategy, were based on cumulative analyses of individual models developed for the Critical Quality Attributes (23 Glycan Profiles) considered for the study. The analyses of the CQA estimates and model performances were inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In summary the results of this study show that the combination of Raman spectroscopy with chemometrics models is a suitable method for real‐time measurement of amino acids in cell culture processes. The presented PAT platform can be seen as a step towards the real‐time monitoring and control of product quality attributes by regulating the amino acid feed in cell culture media . The developed models can be further optimized to reduce the errors.…”
Section: Discussionmentioning
confidence: 99%
“…In summary the results of this study show that the combination of Raman spectroscopy with chemometrics models is a suitable method for real‐time measurement of amino acids in cell culture processes. The presented PAT platform can be seen as a step towards the real‐time monitoring and control of product quality attributes by regulating the amino acid feed in cell culture media . The developed models can be further optimized to reduce the errors.…”
Section: Discussionmentioning
confidence: 99%
“…The initial CQA assessment will leverage literature, prior knowledge, and the target product profile to develop a preliminary set of CQAs and critical process parameters. During product development, as more knowledge is gathered for all quality attributes including the CQAs, the critical process parameters should be defined [183][184][185] and controlled to deliver a product that satisfies the intended target product profile.…”
Section: Discussionmentioning
confidence: 99%
“…Ren et al (2019) have demonstrated the use of the K‐means clustering method to identify the similarities of historical pharmaceutical batches. Data‐driven advanced analytics for process modeling (Kornecki & Strube, 2019), process design space analysis (Bhatia et al, 2016), and the connection between CPPs and CQAs have been covered elsewhere (Sokolov et al, 2016; Sokolov et al, 2017).…”
Section: Data Automation Visualization and Smart Data Utilitymentioning
confidence: 99%